Using Theory of Change to evaluate the role of stakeholder engagement towards socially desirable outcomes in ICT research projects - Jiya, Tilimbe (International Journal of Information Systems and Project Management, 2021)
Information Communication Technologies (ICT) research projects are important in generating breakthrough technologies that translate into solutions for numerous societal grand challenges through research and innovation (R&I). However, to ensure that such solutions are socially desirable, there is a concerted drive for the engagement of different stakeholders, including industry, academia, public and government. In the face of the growing recognition of stakeholder engagement in ICT research projects, particularly as part of Responsible Research and Innovation (RRI), there is a limited discourse on how its consequence could be evaluated. This paper suggests and uses a Theory of Change approach to evaluate the value of stakeholder engagement on the attainment of socially desirable and responsible outcomes in projects, particularly ICT research projects. Using a multi-case study approach, the paper appraises the value of stakeholder engagement in ICT research projects by elucidating the linkages between stakeholder activities and socially desirable outcomes. The findings from the paper could apply to other types of projects apart from ICT research projects in understanding some of the roles stakeholders play in ensuring responsible innovation as an outcome of the projects.